Situation Report: Hungary, 25 February 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Party Official's Radio Interview Focuses on Soviet Reform and Romania / by Alfred Reisch Party Attempts to Split Writers' Union Yugoslav Daily Discusses Literary Conflicts in Hungary / by Slobodan Stankovic Writers' Union Remains under Fire New Trade Union for Free-Lancers and Other Writers / by Alfred Reisch New Measures to Combat Drug Abuse / by Edith Markos Full Employment Versus Economic Efficiency / by Karoly Okolicsanyi